MANAGING ARTHRITIS JOINT PAIN AND HYPERTENSION IN ELDERLY WITH HEALTH EDUCATION VIDEO - Budhyanti, Weeke; Anggiat, Lucky; Juwita, Citra Puspa (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of  the study. Arthritis of the joint and hypertension are two conditions that the elderly are prone to face. Both of these conditions affect the movement and function of the human body. The Physiotherapy study program considers it important to continue to provide service to the elderly community in Kelurahan Cawang, which is a fostered area of the Fakultas Vokasi. Materials and methods. Program socialization with health education videos for the elderly exercises for arthritis pain and hypertension were options to continue providing community service during a pandemic. Empowerment of public health agents and families is also carried out to disseminate information about the health of the elderly in terms of hypertension and arthritis pain which are prepared by lecturers of the physiotherapy study program. Results. With the health educational video, the elderly still pay attention to their health even though they are not as effective as usual. Conclusions. As the conclusion, the elderly still felt helped and were enthusiastic about participating in the health educational videos provided by the lecturers.